By Whom the History Was Invented? - Juchnevičienė, Nijolė (Literatūra, 2012)
The present article aims to question the frequent attitude towards the problem of the beginnings of Western historical thinking and the Western tradition of historiography in the contemporary scientific discourse. The term “historical thinking” includes the interest in historical knowledge as such, the inquiry that engages with the past, understanding how the past conditions the present, the concept of time, and the idea of social change in the flow of time. The article shows that the writings of Herodotus and Thucydides are the generative matrix of Western historical thought, because they took up their task as a very important one both for the author and for his society. The modern cliché which defines the Greek concept of time as a cycle has proof neither in Herodotus nor in Thucydides: historical events in their Histories are presented as unfolding in a linear fashion, and their focus of interest begins to shift from the past to the present. The most important contribution to the historical concept of time is that they excluded sacred, mythical time from spatium historicum. Secondly, their Histories are the histories of change: Herodotus’ History is concerned with developments involving many states and countries; it is the first universal history ever written and bears the evidence of the “singularization of history”, which had been preceded by the singularization of the political world. Thucydides’ History is a history of a radical social and cultural change. They were the first to write history when our idea of history did not exist. One of the greatest vices of the contemporary scientific debate is that this debate is based primarily on the modern understanding of history and historiography.